Effects of different soil water holding capacities on vegetable residue return and its microbiological mechanism - Lu, Chao; Zhu, Qian; Qiu, Meihua; Fan, Xinhui; Luo, Jia; Liang, Yonghong; Ma, Yan (Frontiers in Microbiology, 2023)
With the gradual expansion of the protected vegetable planting area, dense planting stubbles and increasing labor cost, the treatment of vegetable residues has become an urgent problem to be solved. Soil bacterial community structure plays an important role in vegetable residue return and is susceptible to environmental changes. Therefore, understanding the influences of different soil water holding capacities on plant residue decomposition and soil bacterial communities is important for biodegradation. During the whole incubation period, the weight loss ratio of plant residue with 100% water holding capacity was 69.60 % to 75.27%, which was significantly higher than that with 60% water holding capacity in clay and sandy soil, indicating that high water holding capacity promoted the decomposition of plant residue. The degradation of lignin and cellulose was also promoted within 14 days. Furthermore, with the increase in soil water holding capacity, the contents of NH4+ increased to 5.36 and 4.54 times the initial value in the clay and sandy soil, respectively. The increase in napA and nrfA resulted in the conversion of NO3- into NH4+. The increase in water holding capacity made the bacterial network structure more compact and changed the keystone bacteria. The increase in water holding capacity also increased the relative abundance of Firmicutes at the phylum level and Symbiobacterium, Clostridium at the genus level, which are all involved in lignin and cellulose degradation and might promote their degradation. Overall, these findings provide new insight into the effects of different soil water holding capacities on the degradation of plant residues in situ and the corresponding bacterial mechanisms.